ENT 530 Social Media Portfolio: De’Aroma / Mohamad Adam Arif Mohamad - Mohamad, Mohamad Adam Arif (2021)
De’Aroma is a company which is focusing on selling a natural scented candle. It all started when the owner of this company felt like most of the scented candle in Malaysia is expensive and so he decided to make his own. At ﬁrst he do it for fun and after he give some of it to his family and friends, they encourage him to sell it online. It all started in early of March 2021 in Port Klang. The objective of the company is to create a scented candle that can be use in any occasion. The target market for this product is for teenagers and woman and it is only RM35 each. The tagline for this company is “The smell of happiness.” The mission of this company is Be you natural candle making of your choice that produce high quality of ingredient of scented candle that will inspire your sense with wonderful aroma. While some of the vision is in the short term, we aims to become one of the best scented candle making company in the country. De’Aroma use Facebook as a platform to run the business and it is a huge opportunity to post all of the product either as a Teaser, Hard Sell and Soft Sell. It is a great platform to expand the business and the best part is it is free to use. So we can cut a lot of cost for it. Lastly, we are hoping that De’Aroma will be a successful company in the future.